DAKWAH DAN MODERASI BERAGAMA SIVITAS AKADEMIK INSTITUT AGAMA ISLAM NEGERI FATTAHUL MULUK PADA MASYARAKAT DI PAPUA - Siswanto, Eko (MIYAH : Jurnal Studi Islam, 2024)
Abstract: This study aims to identify and explore the mainstreaming of religious moderation da'wah values by the academic community of the Fattahul Muluk Papua State Islamic Institute in the community. Data collection uses interview, observation, and documentation techniques. This study concludes the role of the academic community of the Fattahul Muluk Papua State Islamic Institute in actively contributing to the development of moderate religious life in the community through various forms, including the mainstreaming of the value of tolerance and anti-radicalism through the role of lecturers and alumni, both in the activities of taklim assemblies, community organizations, and scientific research publications. Then, the mainstreaming of the value of national commitment through the cooperation program of Fattahul Muluk Papua State Islamic Institute with government institutions in the dissemination of the values of strengthening nationalism. Furthermore, the mainstreaming of accommodating values to local culture through the collaboration program of Fattahul Muluk State Islamic Institute with the Ministry of Religious Affairs and the Forum for Religious Harmony in appreciating and preserving a variety of local cultural wisdom. The theoretical implications of this study show that the role of universities in Indonesia in mainstreaming the values of religious moderation can be manifested through various cooperation programs related to social, religious, academic, cultural, and political activities. Keywords: State Islamic Institute of Fattahul Muluk Papua, value mainstreaming, religious moderation